1994
DOI: 10.1088/0031-9155/39/3/015
|View full text |Cite
|
Sign up to set email alerts
|

The importance and implementation of accurate 3D compensation methods for quantitative SPECT

Abstract: The purpose of this study was to investigate the importance of 2D versus 3D compensation methods in SPECT. The compensation methods included in the study addressed two important degrading factors, namely attenuating and collimator-detector response in SPET. They can be divided into two general categories. The conventional methods are based on the filtered backprojection algorithm, the Chang algorithm for attenuation compensation and the Metz filter for detector response compensation. These methods, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(72 citation statements)
references
References 38 publications
6
64
0
2
Order By: Relevance
“…The effects of statistical noise in iterative SPECT reconstruction have been studied [2]. So too have the effects of modeling or not modeling scatter, detector response, and attenuation [1], [3]. One area that has received less attention is the consequences of incorrect modeling of imagingsystem properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of statistical noise in iterative SPECT reconstruction have been studied [2]. So too have the effects of modeling or not modeling scatter, detector response, and attenuation [1], [3]. One area that has received less attention is the consequences of incorrect modeling of imagingsystem properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, if optimal corrections for image degradations induced by SPECT physical phenomena such as depth-dependent blur, photon attenuation, and scatter are needed, iterative image reconstruction is to be used (1). It was shown by Gilland et al (3), Tsui et al (4,5), and Rosenthal et al (6), for example, that these corrections reduce errors for absolute quantification in SPECT. Both the availability of fast computers at low cost and advances in efficient processing allow the use of computationally expensive iterative methods in clinical routine (1).…”
mentioning
confidence: 99%
“…It has been demonstrated that, with appropriate SPECT acquisition, calibration, and quantitative reconstruction, SPECT can provide accurate estimates of in vivo radioactivity distributions. [19][20][21][22] Although quantitative SPECT ͑QSPECT͒ may become the method of choice for quantifying in vivo activity distribution, it is currently difficult to implement clinically because of the more complex imaging protocol required to cover the dosimetrically important organs, the longer acquisition times conventionally used, and the need to use computationally intensive iterative reconstruction methods. In order to address some limitations of the QSPECT method, we have developed a new quantitative planar ͑QPlanar͒ method which is based on maximum-likelihood estimation of organ activities using 3D organ VOIs and a model-based projector that models image degrading effects including attenuation, scatter, and the full collimator-detector response.…”
mentioning
confidence: 99%